COVID-19 to Green Entrepreneurial Intention: Role of Green Entrepreneurial Self-Efficacy, Optimism, Ecological Values, Social Responsibility, and Green Entrepreneurial Motivation - Wang, Wenke; Cao, Qilin; Zhuo, Chaoyang; Mou, Yunhan; Pu, Zihao; Zhou, Yunhuan (Frontiers in Psychology, 2021)
This study investigated the impact of the COVID-19 pandemic on the green entrepreneurial intention of college students through green entrepreneurial self-efficacy, optimism, ecological values, and social responsibility, as well as the mediating role of green entrepreneurial motivation. This study used structural equation model to test the hypothesis on samples of 410 Chinese colleges’ students. The research results showed that COVID-19 had a significant positive impact on green entrepreneurial self-efficacy, optimism, ecological values, and social responsibility. Among them, optimism and social responsibility had a significant positive impact on green entrepreneurial self-efficacy, and green entrepreneurial motivations also positively and significantly moderated the relationship between optimism, ecological values, social responsibility and green entrepreneurial intention. The results also show that there is a significant positive correlation between green entrepreneurial self-efficacy and optimism, and there is a significant positive correlation between ecological values and social responsibility.